ANALISIS PUTUSAN PKPU PADA PT.ASURANSI JIWA KRESNA: (Studi Putusan Pengadilan Niaga Nomor 389/Pdt.Sus-PKPU/2020 /PN-Niaga.Jkt.Pst.) - Marva Yordana Ashila Rashid; Zainal Asikin; Diman Ade Mulada (Commerce Law, 2021)
This study argues that the Commercial Court Decision NO 389/Pdt.Sus-PKPU/2020/PN-Niaga.Jkt.Pst has inadequate legal consideration, as well as identifies the legal standing of insurance holders that file the case of debt payment delay. This study is a normative one. Results of this study show that the regulation for this issue is the Law of Bankruptcy and Debt Payment Delay, Law of Financial Security Authority, Law of Insurance, Supreme Court Decision, and Rules of Financial Security Authority. In addition, the decision granting the plaintiff the delay has inadequate legal consideration, as the only institution eligible for the demand for delay is OJK. In other words, insurance holder is legally ineligible to file the case of delay demand.